2020
DOI: 10.1371/journal.pntd.0008406
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic activity controls cholera outbreaks in the East African Rift

Abstract: We hypothesized that Cholera (Vibrio cholerae) that appeared along Lake Kivu in the African Rift in the seventies, might be controlled by volcano-tectonic activity, which, by increasing surface water and groundwater salinity and temperature, may partly rule the water characteristics of Lake Kivu and promote V. cholerae proliferation. Volcanic activity (assessed weekly by the SO 2 flux of Nyiragongo volcano plume over the 2007-2012 period) is highly positively correlated with the water conductivity, salinity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Mayon in 2018 showed large vegetation and environmental impacts of this eruption, which have affected the whole archipelago up to the northern part of Borneo [ 72 ]. Studies have also stressed the likely impacts of volcanic activities on disease outbreaks [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mayon in 2018 showed large vegetation and environmental impacts of this eruption, which have affected the whole archipelago up to the northern part of Borneo [ 72 ]. Studies have also stressed the likely impacts of volcanic activities on disease outbreaks [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sweden and Finland experienced extremely warm summers that corresponded with high SST and an increase in human Vibrio infections in 2014 . Volcanic activity has even been associated with increased V. cholerae in freshwater lakes and with corresponding fluctuations in nearby cholera cases due to changes in water temperature and other chemical factors . Overall, climate change has the potential to expand the ecological niche of V. cholerae , and an increase in natural disasters can increase the risk of waterborne diseases .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…139 Volcanic activity has even been associated with increased V. cholerae in freshwater lakes and with corresponding fluctuations in nearby cholera cases due to changes in water temperature and other chemical factors. 140 Overall, climate change has the potential to expand the ecological niche of V. cholerae, and an increase in natural disasters can increase the risk of waterborne diseases. 141 Models of global climate change can help predict where V. cholerae outbreaks could become more common.…”
Section: ■ Environmental Risk Factorsmentioning
confidence: 99%
“…A separate study has also found that increased cholera case numbers, conflicts, and internally displaced persons in endemic areas in the east were associated with an increased risk of cholera diffusing outside of eastern provinces [ 39 ]. Regarding environmental conditions in eastern provinces, most of the lakes in eastern DRC are of tectonic origin, with physico-chemical properties conducive to the survival of Vibrio cholerae [ 40 ]. Thus, an aquatic environmental reservoir in the east with physico-chemical conditions that support toxigenic forms of Vibrio cholerae [ 41 ], combined with poor access to safe drinking water and proper sanitation facilities, may drive continuous exchange between humans and the environment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%